2003
DOI: 10.1056/nejmoa030288
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Study of Bortezomib in Relapsed, Refractory Myeloma

Abstract: Bortezomib, a member of a new class of anticancer drugs, is active in patients with relapsed multiple myeloma that is refractory to conventional chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
1,761
13
36

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,417 publications
(1,910 citation statements)
references
References 31 publications
70
1,761
13
36
Order By: Relevance
“…Bortezomib (Velcade™; PS-341) is a potent inhibitor of myeloma cell growth and survival in vitro and results indicate striking therapeutic efficacy and acceptable toxicity profile of intravenous bortezomib in myeloma patients when administered alone or in combination with dexamethasone and/or chemotherapeutic agents, after relapse or at first presentation (70)(71)(72)(73)(74). In addition to myeloma cells, osteoblasts are also sensitive to proteasome inhibitors, and we have recently shown that structurally-unrelated inhibitors of the ubiquitin-proteasome pathway (including bortezomib) have beneficial anabolic effects on the skeleton in vivo (60,75).…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
“…Bortezomib (Velcade™; PS-341) is a potent inhibitor of myeloma cell growth and survival in vitro and results indicate striking therapeutic efficacy and acceptable toxicity profile of intravenous bortezomib in myeloma patients when administered alone or in combination with dexamethasone and/or chemotherapeutic agents, after relapse or at first presentation (70)(71)(72)(73)(74). In addition to myeloma cells, osteoblasts are also sensitive to proteasome inhibitors, and we have recently shown that structurally-unrelated inhibitors of the ubiquitin-proteasome pathway (including bortezomib) have beneficial anabolic effects on the skeleton in vivo (60,75).…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
“…Due to generally higher levels of proteasome activity in cancer cells, inhibition of the proteasome elicits pro‐apoptotic effects preferentially in malignant cells compared with normal cells, and is a well‐validated target in multiple myeloma (MM). Three proteasome inhibitors (PIs), bortezomib (BTZ: Kane et al , 2003; Richardson et al , 2003, 2005), carfilzomib (CFZ) and ixazomib (IXZ) are currently approved for the treatment of MM, with several others in development. Although important therapeutic advances, these PIs are associated with significant and dose‐limiting off‐target toxicities (Lonial et al , 2005; Richardson et al , 2006; Cai et al , 2014; Harvey, 2014; Atrash et al , 2015; Wanchoo et al , 2015) and the development of acquired resistance (Fall et al , 2014; Huber et al , 2015; Niewerth et al , 2015).…”
mentioning
confidence: 99%
“…45,46 Common toxicities include sometimes severe gastrointestinal effects (usually diarrhea and less often constipation), sensory peripheral neuropathy, and orthostatic hypotension. Studies have shown that administering bortezomib once weekly instead of twice weekly reduces gastrointestinal and neuropathic toxicity by roughly 30%, 47 and subcutaneous instead of intravenous administration similarly reduces toxicity.…”
Section: Side Effects and Supportive Carementioning
confidence: 99%